2017
DOI: 10.3892/or.2017.5746
|View full text |Cite
|
Sign up to set email alerts
|

Vasohibin-1 inhibits angiogenesis and suppresses tumor growth in renal cell carcinoma

Abstract: Vasohibin-1 (VASH1) has recently been isolated as a novel inhibitor of angiogenesis. Several studies have demonstrated that VASH1 plays important roles in tumor angiogenesis but the role of this angiogenic inhibitor in renal cell carcinoma (RCC) has not been elucidated. We previously reported that VASH1 expression is reduced and is associated with clinicopathological features in RCC. In the present study, we investigated the biological effects of VASH1 in RCC by evaluating the effects of VASH1 on cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…We investigated further target genes of miR-181b-2-3p, miR-1226-3p, and miR-1193 because they are not recognized by multiple miRNAs also excluded by the previous analysis, although they belong to the top five categories (see Table 2 ). Concerning the genes recognized by miR-181b-2-3p, we found, in the GO:0071559 category (the response to transforming growth factor β), FGFR2 (fibroblast growth factor receptor 2) and nuclear receptor NR3C1 (nuclear receptor subfamily 3 group C member 1) acting as receptors of glucocorticoids; in GO:0198738 (cell–cell signaling by Wnt), we found FGFR2, the X-linked gene DDX3X (DEAD-box helicase 3 X-linked), and FBXW11 (the F-box and WD repeat domain containing 11) associated with lymphocytic leukemia [ 38 , 54 ] and ROR1 (receptor-tyrosine-kinase-like orphan receptor 1), which is essential during embryogenesis and upregulated in tumors; while CCN1 (cellular communication network factor 1) and the gene coding the new factor VASH1 (vasohibin-1) belong to the GO:0001701 pathway (in utero embryonic development)—they inhibit angiogenesis and are enhanced by VEGF-A and Fibroblast Growth Factor (FGF)-2 [ 55 ] (which is a target of the other miR-1226-3p). Considering the genes interacting with miR-1193, one is included in the GO:0071559 category and encodes cysteine protease USP15 (ubiquitin-specific protease 15), which is significantly expressed at low levels in the chronic myelogenous leukemia cell lines and peripheral blood mononuclear cells of affected patients [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…We investigated further target genes of miR-181b-2-3p, miR-1226-3p, and miR-1193 because they are not recognized by multiple miRNAs also excluded by the previous analysis, although they belong to the top five categories (see Table 2 ). Concerning the genes recognized by miR-181b-2-3p, we found, in the GO:0071559 category (the response to transforming growth factor β), FGFR2 (fibroblast growth factor receptor 2) and nuclear receptor NR3C1 (nuclear receptor subfamily 3 group C member 1) acting as receptors of glucocorticoids; in GO:0198738 (cell–cell signaling by Wnt), we found FGFR2, the X-linked gene DDX3X (DEAD-box helicase 3 X-linked), and FBXW11 (the F-box and WD repeat domain containing 11) associated with lymphocytic leukemia [ 38 , 54 ] and ROR1 (receptor-tyrosine-kinase-like orphan receptor 1), which is essential during embryogenesis and upregulated in tumors; while CCN1 (cellular communication network factor 1) and the gene coding the new factor VASH1 (vasohibin-1) belong to the GO:0001701 pathway (in utero embryonic development)—they inhibit angiogenesis and are enhanced by VEGF-A and Fibroblast Growth Factor (FGF)-2 [ 55 ] (which is a target of the other miR-1226-3p). Considering the genes interacting with miR-1193, one is included in the GO:0071559 category and encodes cysteine protease USP15 (ubiquitin-specific protease 15), which is significantly expressed at low levels in the chronic myelogenous leukemia cell lines and peripheral blood mononuclear cells of affected patients [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…After follow-up, Cox proportional risk regression model analysis showed that VASH1 and lymph node metastasis were independent risk factors for the prognosis of colon cancer patients, respectively. It is noteworthy that, in contrast to the colon cancer study, Zhao et al [25] showed that high VASH1 expression was associated with a better prognosis in renal cell carcinoma. This further indicates that VASH1 has different types of regulatory effects in different types of tumors and tissues.…”
Section: Discussionmentioning
confidence: 85%
“…It is concluded that VASH1 can inhibit the progression of glioma under certain conditions. According to Zhao [35] et al, VASH1 overexpression can inhibit the proliferation and apoptosis of human umbilical cord endothelial cells and 786-0 cells, but it cannot inhibit tumor invasion. We believe that this may be due to different internal microenvironments of different tumor tissues, resulting in changes in the interaction of cytokines such as VASH1.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies investigated whether this critical inhibitor of angiogenesis could serve as a key factor in tumor progression (7,8,12). The potential value of VASH1 in suppressing cancer cell proliferation and invasion has been confirmed by several studies, and antiangiogenic therapy is currently used for several types of cancer (35)(36)(37). Data have also demonstrated that VASH1 expression may inhibit tumorigenesis and metastasis in a human colon cancer model (12).…”
Section: Discussionmentioning
confidence: 95%